Information about expert decision and post‐decision distortion of facts of own decision. Issue 2 (15th December 2017) - Svenson, Ola; Gonzalez, Nichel; Memon, Amina; Lindholm, Torun
Abstract : Cognitive representations of decision problems are dynamic. During and after a decision, evaluations and representations of facts change to support the decision made by a decision maker her‐ or himself (Svenson, 2003). We investigated post‐decision distortion of facts (consolidation). Participants were given vignettes with facts about two terminally ill patients, only one of whom could be given lifesaving surgery. In Study 1, contrary to the prediction, the results showed that facts were distorted after a decision both by participants who were responsible for the decisions themselves and when doctors had made the decision. In Study 2 we investigated the influence of knowledge about expert decisions on a participant's own decision and post‐decisional distortion of facts. Facts were significantly more distorted when the participant's decision agreed with an expert's decision than when the participant and expert decisions disagreed. The findings imply that knowledge about experts' decisions can distort memories of facts and therefore may obstruct rational analyses of earlier decisions. This is particularly important when a decision made by a person, who is assumed to be an expert, makes a decision that is biased or wrong.